Endangered habitats - Tesar, Jenny E. (New York Facts on File, 1992)
Examines the various types of Earth's habitats, the complex relationships of plants and animals found in them, and how man's activities can upset or destroy fragile ecological balances.
Includes bibliographical references (p. 107-108) and index.
Keywords: Habitat (Ecology) -- Juvenile literature; Ecology; Habitat (Ecology); Nature -- Effect of human beings on